A leap towards enforcing medicines prescribing by generic names in low- and middle-income countries (LMICs): pitfalls, limitations, and recommendations for local drug regulatory agencies - Hamid A. Merchant; Zaheer-; Izhar M. Hussain (Taylor & Francis Group, 2022)
The Drug Regulatory Authority of Pakistan (DRAP) in response to the public outcry on increasing medicines prices in the country issued notifications to direct healthcare professionals to prescribe medicines with their generic names. Like DRAP, many regulators in the low- and middle-income countries (LMICs) are also inspiring from the west to legally enforce generic prescribing in a bid to reduce the out-of-pocket public expenditures. However, there are pitfalls in the LMICs drug regulatory framework, which if left unaddressed can severely jeopardise the foreseen benefits of medicines prescribing by generic names. This article critically appraises the impact of prescribing by generic names regulations in LMICs and highlights the key considerations that are vital to address before legally enforcing generic prescribing. The ethics, regulatory compliance, and good governance are the key to success; better generics for a better tomorrow.